Сучасні наукові підходи до вдосконалення державної етнонаціональної політики Російської Федерації - Вітман, Костянтин Миколайович; Витман, Константин Николаевич; Vitman, K. (My University, 2010)
Modern scientiﬁ c approaches to improving the state Ethnic Policy of the Russian Federation are analyzed in the article. It is deﬁ ned that one of the organizational- legal forms of ethnic-national politics is the preparation and implementation of federal and regional programs of national-cultural development of the peoples, which can become a part of the federal and regional social-economic development of the country as a whole or its separate regions.
Вітман К. М. Сучасні наукові підходи до вдосконалення державної етнонаціональної політики Російської Федерації / К. М. Вітман // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України, НУ ОЮА. - Одеса : Фенікс, 2010. - Вип. 40. - С.10-15.
Keywords: етнонаціональна політика Російської Федерації; федеральні і регіональні програми національно-культурного розвитку народів; этнонациональная политика Российской Федерации; федеральные и региональные программы национально-культурного развития народов; Ethnic Policy of the Russian Federation; federal and regional programs of national cultural development of peoples